Carbon-coated hydrated sodium manganese oxide material, preparation method thereof, positive plate and sodium ion battery

By carrying out carbon coating process under low temperature conditions, carbon-coated hydrated sodium-manganese oxide materials are generated, which solves the problem of insufficient conductivity and cycling performance of sodium-manganese oxides, and achieves the effect of high specific capacity and good cycling stability. Suitable for large-scale production and low-cost applications.

CN119480977APending Publication Date: 2025-02-18GUIZHOU WEIFANG ENERGY NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411593702.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the conductivity and cycling performance of sodium-manganese oxides under low cost and large-scale production conditions, resulting in limited application of its sodium-ion batteries.

Method used

Carbon coating process under low temperature conditions is adopted to generate carbon coated hydrated sodium-manganese oxide materials through the steps of carbonization at 600-1100°C and calcining at 250-400°C, which reduces the risk of carbon oxidation and avoids sodium-manganese oxide structure. destroy.

Benefits of technology

It achieves high specific capacity and good cycle stability of sodium-manganese oxide, which is suitable for large-scale production and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480977A_ABST
    Figure CN119480977A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion battery positive electrode materials, in particular to a carbon-coated hydrated sodium manganese oxide material, a preparation method thereof, a positive plate and a sodium ion battery. The method comprises the following steps: mixing a manganese source and an organic carbon source, and carbonizing in an inert atmosphere at 600-1100 DEG C to obtain a first precursor; mixing the first precursor with a sodium source, calcining in an oxygen-containing atmosphere at 250-400 DEG C, and reacting to obtain a second precursor; and soaking the second precursor in water, washing and drying to obtain the carbon-coated hydrated sodium manganese oxide material. And / or mixing a manganese source, a sodium source and an organic carbon source, reacting in an inert atmosphere at 210-280 DEG C, and carbonizing to obtain a carbon-coated sodium manganese oxide precursor; and soaking the carbon-coated sodium manganese oxide precursor in water, washing and drying to obtain the carbon-coated hydrated sodium manganese oxide material. The two methods can weaken the situation that the carbon is oxidized and loses the coating effect, the structure of the sodium manganese oxide is prevented from being damaged, and the process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a carbon-coated hydrated sodium manganese oxide material and a preparation method thereof, a positive electrode sheet and a sodium ion battery. Background Art

[0002] Sodium-ion batteries have the advantages of low cost and high safety, and have great application prospects in fields such as large-scale energy storage and low-speed vehicles.

[0003] The positive electrode material is one of the key materials in sodium-ion batteries and has an important influence on the energy density and cycle performance of sodium-ion batteries. At present, the most studied positive electrode materials for sodium-ion batteries are: transition metal oxides, Prussian blue / white compounds, and polyanion compounds. Sodium manganese oxide belongs to transition metal oxides, which has a large theoretical specific capacity, and due to the abundant resources of sodium and manganese elements, it has the advantages of being able to meet large demands and low raw material costs. However, the electrical conductivity of sodium manganese oxide is low, and it is difficult to meet the requirements for practical use. In order to meet the requirements for practical use, doping and surface coating are currently mainly used to improve the performance of sodium manganese oxide.

[0004] Carbon coating is a common material modification method in the field of new energy materials. Carbon coating of materials can improve the conductivity of materials on the one hand, and provide a stable chemical and electrochemical reaction interface on the other hand, improving the material's cycle performance. Carbon coating of materials using organic matter as a carbon source can obtain a relatively uniform coating layer, and the coating layer and the coated material are firmly bonded, which is conducive to the transmission of ions and electrons.

[0005] However, using organic matter as a carbon source to carbonize sodium manganese oxide requires carbonization at a relatively high temperature and under inert atmosphere protection conditions. Carbon has a strong reducibility under high temperature conditions, and the average valence of manganese in sodium manganese oxide is +3 to +4, which has a certain oxidizing property. Therefore, the carbon generated during the carbonization process will reduce the manganese in the sodium manganese oxide and cause the structure of the sodium manganese oxide to be destroyed.

[0006] Similarly, if the surface of the material is first coated with carbon and then reacted at high temperature to generate sodium manganese oxide, the carbon will be easily oxidized and lose the coating effect (or the coating effect will be poor).

[0007] Patent CN103606654A discloses a method for preparing a carbon-coated manganese oxide composite material, wherein manganese hydroxide or manganese dioxide is mixed with an organic carbon source under inert atmosphere protection and a certain temperature condition to prepare a nano manganese oxide / carbon composite, and then the composite is mixed with acetylene black and PTFE, and evenly coated on a nickel foam electrode, and electrochemical charge and discharge are performed using a constant current technique to prepare a petal-shaped high-performance manganese oxide / carbon composite. The composite carbon prepared by the invention is firmly combined with manganese oxide, has high specific capacity, high power density, and good stability. However, the manganese oxide / carbon composite prepared by the method is difficult to separate from acetylene black, PTFE, and nickel foam, which is not conducive to the further utilization of the material and is not suitable for industrial production.

[0008] Therefore, finding a sodium manganese oxide carbon coating method with a simple preparation process and suitable for large-scale production will be of great significance to promoting the practical and industrial application of sodium manganese oxide, and will play a role in promoting the broader market application of sodium-ion batteries.

[0009] In view of this, the present invention is proposed. Summary of the invention

[0010] The first object of the present invention is to provide a method for preparing a carbon-coated hydrated sodium manganese oxide material, wherein method (a) reacts a sodium source with a precursor of a carbon-coated manganese source under a relatively low calcination temperature to generate sodium manganese oxide, and method (b) synthesizes sodium manganese oxide by a low-temperature reaction and simultaneously carbonizes the sodium manganese oxide at a low temperature to obtain the sodium manganese oxide. In method (a) and method (b) under low-temperature conditions, the reaction activity of carbon is relatively low, which can greatly reduce the occurrence of the situation where carbon is oxidized and loses its coating effect, and can also avoid the destruction of the structure of the sodium manganese oxide; and the two methods are simple in process and easy to realize large-scale production. The carbon-coated hydrated sodium manganese oxide material prepared by the two methods has a relatively high specific capacity and rate performance, as well as good cycle stability.

[0011] The second object of the present invention is to provide a carbon-coated hydrated sodium manganese oxide material, wherein the carbon coating layer is uniformly covered on the surface of the sodium manganese oxide, the coating effect is good, and the carbon-coated hydrated sodium manganese oxide material has high electrical conductivity, high specific capacity and good cycle stability.

[0012] The third object of the present invention is to provide a positive electrode sheet with high capacity and good cycle stability.

[0013] A fourth object of the present invention is to provide a sodium ion battery having high capacity and excellent cycle performance.

[0014] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0015] The present invention first provides a method for preparing a carbon-coated hydrated sodium manganese oxide material, comprising at least one of the following methods (a) and (b): (a) mixing a manganese source and an organic carbon source, and then carbonizing the mixture at 600-1100° C. in an inert atmosphere to obtain a first precursor of the carbon-coated manganese source; mixing the first precursor with a sodium source, and then calcining and reacting the mixture at 250-400° C. in an oxygen-containing atmosphere to obtain a second precursor; soaking the second precursor in water, and then washing and drying the mixture to obtain a carbon-coated hydrated sodium manganese oxide material; (b) mixing a manganese source, a sodium source and an organic carbon source, and then reacting and carbonizing the mixture at 210-280° C. in an inert atmosphere to obtain a carbon-coated sodium manganese oxide precursor; soaking the carbon-coated sodium manganese oxide precursor in water, and then washing and drying the mixture to obtain a carbon-coated hydrated sodium manganese oxide material.

[0016] Furthermore, in method (a), the manganese source includes at least one of MnO2, Mn2O3, Mn3O4 and MnO.

[0017] Furthermore, in method (a), the organic carbon source includes at least one of glucose, sucrose, citric acid and tannic acid.

[0018] Furthermore, in method (a), the sodium source comprises NaOH.

[0019] Furthermore, in method (a), the molar ratio of the manganese element in the manganese source to the carbon element in the organic carbon source is 1:0.15-0.5.

[0020] Furthermore, in method (a), the molar ratio of the manganese element in the manganese source to the sodium element in the sodium source is 1:1-2.

[0021] Furthermore, in method (a), the carbonization time is 2 to 5 hours.

[0022] Furthermore, in method (a), the gas in the inert atmosphere includes at least one of nitrogen, argon and helium.

[0023] Furthermore, in method (a), the calcination time is 5 to 15 hours.

[0024] Furthermore, in method (a), the soaking time is ≥ 12 h.

[0025] Furthermore, in method (b), the manganese source includes MnO2.

[0026] Furthermore, in method (b), the sodium source includes NaOH.

[0027] Furthermore, in method (b), the organic carbon source includes at least one of glucose and tannic acid.

[0028] Furthermore, in method (b), the molar ratio of the manganese element in the manganese source to the sodium element in the sodium source is 1:1-2.

[0029] Furthermore, in method (b), the molar ratio of the manganese element in the manganese source to the carbon element in the organic carbon source is 1:0.05-0.3.

[0030] Furthermore, in method (b), the carbonization time is 5 to 10 hours.

[0031] Furthermore, in method (b), the gas in the inert atmosphere includes at least one of nitrogen, argon and helium.

[0032] Furthermore, in method (b), the soaking time is ≥ 12 h.

[0033] The present invention further provides a carbon-coated hydrated sodium manganese oxide material prepared by the preparation method of the carbon-coated hydrated sodium manganese oxide material, wherein the carbon-coated hydrated sodium manganese oxide material comprises a sodium manganese layered oxide and a carbon coating layer coated on the surface of the sodium manganese layered oxide; the sodium manganese layered oxide comprises Na4Mn 14 O 27 9H2O, NaMn6O 12 ·3H2O and Na 0.55 At least one of Mn2O4·1.5H2O; the carbon content in the carbon-coated hydrated sodium manganese oxide material is 0.2wt.% to 6wt.%.

[0034] The present invention further provides a positive electrode sheet, comprising the carbon-coated hydrated sodium manganese oxide material prepared by the preparation method of the carbon-coated hydrated sodium manganese oxide material, or the carbon-coated hydrated sodium manganese oxide material.

[0035] The present invention also provides a sodium ion battery, comprising the positive electrode sheet.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The present invention provides a method for preparing a carbon-coated hydrated sodium manganese oxide material, wherein method (a) reacts a sodium source with a precursor of a carbon-coated manganese source under a relatively low calcination temperature to generate sodium manganese oxide, and method (b) synthesizes sodium manganese oxide by low-temperature reaction and simultaneously carbonizes at low temperature. Under low-temperature conditions, the reaction activity of carbon is relatively low, which can greatly reduce the occurrence of carbon being oxidized and losing its coating effect, and can avoid the destruction of the structure of the sodium manganese oxide. In addition, the two methods are simple in process and easy to realize large-scale production. The carbon-coated hydrated sodium manganese oxide material prepared by the two methods has a relatively high specific capacity and good cycle stability.

[0038] (2) The method for preparing the carbon-coated hydrated sodium manganese oxide material provided by the present invention has a wide range of raw materials and is inexpensive, which can meet the needs of low cost and large-scale production.

[0039] (3) The method for preparing the carbon-coated hydrated sodium manganese oxide material provided by the present invention has a simple process and is suitable for large-scale batch production.

[0040] (4) The method for preparing the carbon-coated hydrated sodium manganese oxide material provided by the present invention has a short preparation process and low energy consumption.

[0041] (5) The carbon-coated hydrated sodium manganese oxide material prepared by the preparation method of the carbon-coated hydrated sodium manganese oxide material provided by the present invention has the advantages of high specific capacity and good cycle performance after being assembled into a sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 The XRD pattern of the carbon-coated hydrated sodium manganese oxide material prepared in Example 1 provided by the present invention;

[0044] Figure 2 The XRD pattern of the carbon-coated hydrated sodium manganese oxide material prepared in Example 2 provided by the present invention;

[0045] Figure 3 This is a TEM image of the carbon-coated hydrated sodium manganese oxide material obtained in Example 2 provided by the present invention;

[0046] Figure 4 This is the XRD pattern of the carbon-coated hydrated sodium manganese oxide material prepared in Example 3 provided by the present invention;

[0047] Figure 5 The XRD pattern of the carbon-coated hydrated sodium manganese oxide material prepared in Example 4 provided by the present invention;

[0048] Figure 6 The XRD pattern of the carbon-coated hydrated sodium manganese oxide material prepared in Example 5 provided by the present invention;

[0049] Figure 7 The XRD pattern of the carbon-coated hydrated sodium manganese oxide material prepared in Example 6 provided by the present invention;

[0050] Figure 8 This is the XRD pattern of the carbon-coated hydrated sodium manganese oxide material prepared in Example 7 provided by the present invention;

[0051] Fig. 9 The XRD diagram of the material obtained in Comparative Example 1 provided by the present invention;

[0052] Fig.10 The XRD diagram of the material obtained in Comparative Example 2 provided by the present invention;

[0053] Fig.11 This is the XRD diagram of the material prepared in Comparative Example 3 provided by the present invention. DETAILED DESCRIPTION

[0054] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0055] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0056] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0057] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0058] In a first aspect, the present invention provides a method for preparing a carbon-coated hydrated sodium manganese oxide material, comprising at least one of the following methods (a) and (b):

[0059] (a) mixing a manganese source and an organic carbon source, and carbonizing the mixture at 600-1100° C. in an inert atmosphere to obtain a first precursor of a carbon-coated manganese source; mixing the first precursor of the carbon-coated manganese source with a sodium source, and calcining and reacting the mixture at 250-400° C. in an oxygen-containing atmosphere, and cooling the mixture to obtain a second precursor; soaking the second precursor in water, filtering and washing the mixture to neutrality after a period of time, and then drying (e.g., baking) to obtain a carbon-coated hydrated sodium manganese oxide material.

[0060] In method (a), the carbonization temperature includes but is not limited to any one of 600°C, 700°C, 800°C, 900°C, 1000°C, and 1100°C, or a range between any two of them; the calcination temperature includes but is not limited to any one of 250°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, and 400°C, or a range between any two of them.

[0061] In the method (a) of the preparation method of the carbon-coated hydrated sodium manganese oxide material of the present invention, a carbon-coated manganese source is first obtained by high-temperature carbonization. Since the carbonization temperature is high, the carbonization of organic matter is more complete. Then, a low-temperature calcination method is adopted to react the sodium source with the precursor of the carbon-coated manganese source under relatively low temperature conditions to generate sodium manganese oxide. Under such temperature conditions, the reaction activity of carbon is relatively low, thereby greatly reducing the occurrence of the situation where the carbon is oxidized and loses the coating effect, and the destruction of the structure of the sodium manganese oxide can be avoided.

[0062] Furthermore, method (a) in the preparation method of carbon-coated hydrated sodium manganese oxide material has the following advantages: the raw materials are widely available and cheap, which can meet the requirements of low cost and large-scale production; it adopts a solid-phase production method, which has a simple process and is suitable for large-scale batch production.

[0063] In addition, the carbon-coated hydrated sodium manganese oxide material prepared by method (a) has the advantages of high specific capacity and good cycle performance after being assembled into a sodium ion battery.

[0064] (b), mixing a manganese source, a sodium source and an organic carbon source, reacting and carbonizing at 210-280° C. in an inert atmosphere, and obtaining a carbon-coated sodium manganese oxide precursor after cooling; soaking the carbon-coated sodium manganese oxide precursor in water, filtering and washing to neutrality after a period of time, and then drying (e.g., baking) to obtain a carbon-coated hydrated sodium manganese oxide material.

[0065] Method (b) in the method for preparing the carbon-coated hydrated sodium manganese oxide material of the present invention adopts a low-temperature reaction to synthesize sodium manganese oxide and simultaneously performs low-temperature carbonization (i.e., the synthesis reaction of sodium manganese oxide and the low-temperature carbonization are performed simultaneously), which can greatly reduce the occurrence of carbon being oxidized and losing the coating effect, and avoid the destruction of the sodium manganese oxide structure.

[0066] Furthermore, method (b) in the preparation method of carbon-coated hydrated sodium manganese oxide material has the following advantages: carbonization of organic matter and synthesis of sodium manganese oxide are completed at one time, and the preparation process is short; the raw materials are widely available and cheap, meeting the requirements of low cost and large-scale production; the material is prepared by a low-temperature solid-phase method, which has a simple process and low energy consumption and is suitable for large-scale batch production.

[0067] In addition, the carbon-coated hydrated sodium manganese oxide material prepared by method (b) has the advantages of high specific capacity and good cycle performance after being assembled into a sodium ion battery.

[0068] In some specific embodiments, in method (a), the manganese source includes at least one of MnO2, Mn2O3, Mn3O4 and MnO.

[0069] In some specific embodiments, in method (a), the organic carbon source includes at least one of glucose, sucrose, citric acid and tannic acid.

[0070] In some specific embodiments, in method (a), the sodium source comprises NaOH.

[0071] In some specific embodiments, in method (a), the molar ratio of the manganese element in the manganese source to the carbon element in the organic carbon source is 1:0.15 to 0.5; including but not limited to any point value of 1:0.15, 1:0.2, 1:0.3, 1:0.4, 1:0.5 or any range value between two of them. The carbon coating layer obtained by using the above amount of organic carbon source is of suitable thickness, which is beneficial to improve the conductivity, capacity and cycle performance of the carbon-coated hydrated sodium manganese oxide material.

[0072] In some specific embodiments, in method (a), the molar ratio of the manganese element in the manganese source to the sodium element in the sodium source is 1:1 to 2, including but not limited to any point value of 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2 or a range value between any two of them.

[0073] It is understandable that in the present invention, when the second precursor is immersed in water, some sodium ions will precipitate from the material into the water, and water molecules will enter the material to form crystal water. Due to the presence of water molecules, the material structure is more stable, which is conducive to improving the battery cycle life.

[0074] In some specific embodiments, in method (a), the carbonization time is 2 to 5 hours, including but not limited to any one of 2 hours, 3 hours, 4 hours, and 5 hours, or a range between any two of them.

[0075] In some specific embodiments, in method (a), the gas in the inert atmosphere includes at least one of nitrogen, argon and helium.

[0076] In some specific embodiments, in method (a), the volume fraction of oxygen in the inert atmosphere is ≤ 0.1%.

[0077] In some specific embodiments, in method (a), the calcination time is 5 to 15 hours, including but not limited to any one of 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, and 15h, or a range between any two of them.

[0078] In some specific embodiments, in method (a), the soaking time is ≥ 12 h, such as 15 h, 18 h or 24 h.

[0079] In some specific embodiments, in method (a), the mixing method includes any method commonly used in the art, so as to achieve relatively uniform mixing of the materials. Existing technologies can be used for mixing, such as grinding mixing, ball milling mixing, high-speed mixing, and solid-liquid mixing followed by spray drying.

[0080] In some specific embodiments, in method (a), the mixing method of mixing the precursor of the carbon-coated manganese source with the sodium source is preferably a method of spray drying after solid-liquid mixing.

[0081] In some specific embodiments, in method (a), the step of mixing the manganese source and the organic carbon source and then carbonizing them at 600-1100° C. in an inert atmosphere can be performed multiple times, that is, multiple coating and carbonization are performed to obtain a precursor with a better coating effect.

[0082] In some specific embodiments, in method (a), the oxygen-containing atmosphere includes air atmosphere and / or oxygen atmosphere.

[0083] In some specific embodiments, in method (a), the equipment used for calcination can be existing equipment such as a muffle furnace, a rotary kiln, a tunnel kiln, etc., and the present invention is not limited to this.

[0084] In some specific embodiments, in method (a), after obtaining the carbon-coated hydrated sodium manganese oxide material, it can be washed and filtered to remove soluble substances in the material.

[0085] In some specific embodiments, in method (a), the prepared carbon-coated hydrated sodium manganese oxide material is subjected to XRD analysis, and its main diffraction peak is similar to that of Na4Mn 14 O 27 9H2O, NaMn6O 12 ·3H2O and Na0.55 At least one of Mn2O4·1.5H2O corresponds.

[0086] In some specific embodiments, in method (b), the manganese source includes MnO2. Since the valence of manganese in the calcined product is between +3 and +4, the atmosphere protection is an oxygen-free environment, and the carbon generated after the carbonization of organic matter has a certain reducibility, manganese is reduced during the reaction and the valence will decrease, so the present application uses MnO2 with a valence of +4.

[0087] In some specific embodiments, in method (b), the sodium source comprises NaOH.

[0088] In some specific embodiments, in method (b), the organic carbon source includes at least one of glucose and tannic acid.

[0089] In some specific embodiments, in method (b), the molar ratio of the manganese element in the manganese source to the sodium element in the sodium source is 1:1-2; including but not limited to any point value of 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2 or a range value between any two of them.

[0090] It is understandable that in the present invention, the carbon-coated sodium manganese oxide precursor is immersed in water, and some sodium ions will precipitate from the material into the water, while water molecules enter the material to form crystal water. Due to the presence of water molecules, the material structure is more stable, which is conducive to improving the battery cycle life.

[0091] In some specific embodiments, in method (b), the molar ratio of the manganese element in the manganese source to the carbon element in the organic carbon source is 1:0.05 to 0.3, including but not limited to any point value of 1:0.05, 1:0.1, 1:0.2, 1:0.3 or a range value between any two of them.

[0092] In some specific embodiments, in method (b), the carbonization time is 5 to 10 hours, including but not limited to any one of 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, and 10 hours, or a range between any two of them.

[0093] In some specific embodiments, in method (b), the gas in the inert atmosphere includes at least one of nitrogen, argon and helium.

[0094] In some specific embodiments, in method (b), the soaking time is ≥ 12 h, such as 14 h, 15 h, 18 h or 24 h.

[0095] In some specific embodiments, in method (b), the volume fraction of oxygen in the inert atmosphere is ≤0.1%.

[0096] In some specific embodiments, in method (b), the mixing method includes any method commonly used in the art, so as to achieve relatively uniform mixing of the materials. Existing technologies can be used for mixing, such as grinding mixing, ball milling mixing, high-speed mixing, and solid-liquid mixing followed by spray drying, but are not limited thereto.

[0097] In some specific embodiments, in method (b), after obtaining the carbon-coated hydrated sodium manganese oxide material, it can be washed and filtered to remove soluble substances in the material.

[0098] In some specific embodiments, in method (b), the prepared carbon-coated hydrated sodium manganese oxide material is subjected to XRD analysis, and its main diffraction peak is similar to that of Na4Mn 14 O 27 9H2O, NaMn6O 12 ·3H2O and Na 055 At least one of Mn2O4·1.5H2O corresponds.

[0099] In a second aspect, the present invention provides a carbon-coated hydrated sodium manganese oxide material obtained by the preparation method of the carbon-coated hydrated sodium manganese oxide material. The carbon-coated hydrated sodium manganese oxide material comprises a sodium manganese layered oxide and a carbon coating layer coated on the surface of the sodium manganese layered oxide.

[0100] Wherein, the sodium manganese layered oxide comprises Na4Mn 14 O 27 9H2O, NaMn6O 12 ·3H2O and Na 0.55 At least one of Mn2O4·1.5H2O.

[0101] The mass fraction of carbon element in the carbon-coated hydrated sodium manganese oxide material is 0.2wt.% to 6wt.%, including but not limited to any one of 0.2wt.%, 0.3wt.%, 0.5wt.%, 0.8wt.%, 1wt.%, 1.5wt.%, 2wt.%, 2.5wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt% or a range between any two of them.

[0102] The carbon-coated hydrated sodium manganese oxide material provided by the invention has a carbon coating layer uniformly covering the surface of the sodium manganese oxide, and has a good coating effect.

[0103] In addition, the carbon-coated hydrated sodium manganese oxide material has high electrical conductivity, high specific capacity and good cycle stability.

[0104] In a third aspect, the present invention provides a positive electrode sheet, comprising the carbon-coated hydrated sodium manganese oxide material prepared by the preparation method of the carbon-coated hydrated sodium manganese oxide material, or the carbon-coated hydrated sodium manganese oxide material.

[0105] The positive electrode sheet has high capacity and good cycle stability.

[0106] Optionally, the positive electrode sheet further includes a conductive agent and / or a binder, which is not limited in the present invention.

[0107] In a fourth aspect, the present invention provides a sodium ion battery comprising the positive electrode sheet.

[0108] This sodium ion battery has high capacity and excellent cycle performance.

[0109] Optionally, the positive electrode sheet further includes a negative electrode sheet, a separator and an electrolyte, which is not limited in the present invention.

[0110] In some specific embodiments, the carbon-coated hydrated sodium manganese oxide material is made into a positive electrode sheet for a sodium ion battery after pulping, coating, drying, compacting, cutting and other processes, and is further assembled with a negative electrode sheet, a separator, an electrolyte and the like to form a sodium ion battery.

[0111] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0112] Example 1

[0113] The preparation method of the carbon-coated hydrated sodium manganese oxide material provided in this embodiment is method (a), which specifically includes the following steps: using MnO, NaOH and glucose as manganese source, sodium source and organic carbon source. The mass of the manganese source and the organic carbon source is calculated and weighed according to the molar ratio of manganese element to carbon element of 1:0.15, and then mixed to obtain a mixture, and the mixture is carbonized at 600°C for 5h in an argon protective atmosphere to obtain a first precursor of the carbon-coated manganese source. The mass of the sodium source is calculated and weighed according to the molar ratio of manganese element to sodium element of 1:1.5, and then the sodium source is mixed evenly with the first precursor of the carbon-coated manganese source, and calcined at 350°C for 10h in an air atmosphere to obtain a second precursor. The second precursor is placed in deionized water and soaked for 12h, then filtered, washed to neutrality, and dried to obtain a carbon-coated hydrated sodium manganese oxide material. The carbon-coated hydrated sodium manganese oxide material prepared in this embodiment includes a sodium manganese layered oxide and a carbon coating layer coated on the surface of the sodium manganese layered oxide.

[0114] The carbon-coated hydrated sodium manganese oxide material prepared in this example was subjected to XRD analysis. The analysis results are shown in the attached Figure 1 , and its diffraction peaks are similar to Na 0.55 Mn2O4·1.5H2O (PDF43-1456), that is, the chemical formula of sodium manganese layered oxide is Na 0.55 Mn2O4·1.5H2O. Carbon and sulfur analysis of the material revealed a carbon content of 0.25 wt.%.

[0115] Example 2

[0116] The preparation method of the carbon-coated hydrated sodium manganese oxide material provided in this embodiment is method (a), which specifically includes the following steps: using MnO2, NaOH and tannic acid as manganese source, sodium source and organic carbon source. The mass of the manganese source and the organic carbon source is calculated and weighed according to the molar ratio of manganese element to carbon element of 1:0.5, and then mixed to obtain a mixture, and the mixture is carbonized at 1000°C for 3h in a helium protective atmosphere to obtain a first precursor of the carbon-coated manganese source. The mass of the sodium source is calculated and weighed according to the molar ratio of manganese element to sodium element of 1:1, and then the sodium source is mixed evenly with the first precursor of the carbon-coated manganese source, and calcined at 400°C for 5h in an air atmosphere to obtain a second precursor. The second precursor is placed in deionized water and soaked for 15h, then filtered, washed to neutrality, and dried to obtain a carbon-coated hydrated sodium manganese oxide material. The carbon-coated hydrated sodium manganese oxide material prepared in this embodiment includes a sodium manganese layered oxide and a carbon coating layer coated on the surface of the sodium manganese layered oxide.

[0117] The carbon-coated hydrated sodium manganese oxide material prepared in Example was subjected to XRD analysis. The analysis results are shown in the attached Figure 2 , and its diffraction peaks are similar to Na 0.55 Mn2O4·1.5H2O (PDF43-1456), that is, the chemical formula of sodium manganese layered oxide is Na 0.55 Mn2O4·1.5H2O. The carbon and sulfur analysis of the material showed that the carbon content was 0.54wt%. The TEM test of the material was performed, and the test results are attached. Figure 3 , the carbon coating on the particle surface can be clearly seen, and its thickness is about 2.5nm.

[0118] Example 3

[0119] The preparation method of the carbon-coated hydrated sodium manganese oxide material provided in this embodiment is method (a), comprising the following steps: using Mn3O4, NaOH and sucrose as manganese source, sodium source and organic carbon source. The mass of the manganese source and the organic carbon source is calculated and weighed according to the molar ratio of manganese element to carbon element of 1:0.3, and then mixed to obtain a mixture, and the mixture is carbonized at 1100°C for 2h in a nitrogen protective atmosphere to obtain a first precursor of the carbon-coated manganese source. The mass of the sodium source is calculated and weighed according to the molar ratio of manganese element to sodium element of 1:2, and then the sodium source is mixed evenly with the first precursor of the carbon-coated manganese source, and calcined at 250°C for 15h in an air atmosphere to obtain a second precursor. The second precursor is placed in deionized water and soaked for 14h, then filtered, washed to neutrality, and dried to obtain a carbon-coated hydrated sodium manganese oxide material. The carbon-coated hydrated sodium manganese oxide material prepared in this embodiment includes a sodium manganese layered oxide and a carbon coating layer coated on the surface of the sodium manganese layered oxide.

[0120] The carbon-coated hydrated sodium manganese oxide material prepared in this example was subjected to XRD analysis. The analysis results are shown in the attached Figure 4 It was found that due to the low reaction temperature, the diffraction peak intensity was weak, which was basically the same as that of Na4Mn 14 O 27 9H2O (PDF 23-1046) and NaMn6O 12 ·3H2O (PDF 38-0475) corresponds to the sodium manganese layered oxides including Na4Mn 14 O 27 9H2O and NaMn6O 12 · 3H2O. The material was subjected to carbon and sulfur analysis, and its carbon content was 4.81 wt%.

[0121] Example 4

[0122] The preparation method of the carbon-coated hydrated sodium manganese oxide material provided in this embodiment is method (a), comprising the following steps: using Mn2O3, NaOH and citric acid as manganese source, sodium source and organic carbon source. The mass of the manganese source and the organic carbon source is calculated and weighed according to the molar ratio of manganese element to carbon element of 1:0.2, and then mixed to obtain a mixture, and the mixture is carbonized at 800°C for 4h in an argon protective atmosphere to obtain a first precursor of the carbon-coated manganese source. The mass of the sodium source is calculated and weighed according to the molar ratio of manganese element to sodium element of 1:2, and then the sodium source is mixed evenly with the first precursor of the carbon-coated manganese source, and calcined at 300°C for 12h in an air atmosphere to obtain a second precursor. The second precursor is placed in deionized water and soaked for 14h, then filtered, washed to neutrality, and dried to obtain a carbon-coated hydrated sodium manganese oxide material. The carbon-coated hydrated sodium manganese oxide material prepared in this embodiment includes a sodium manganese layered oxide and a carbon coating layer coated on the surface of the sodium manganese layered oxide.

[0123] The carbon-coated hydrated sodium manganese oxide material prepared in this example was subjected to XRD analysis. The analysis results are shown in the attached Figure 5 , and its diffraction peaks are similar to those of Na4Mn 14 O 27 ·9H2O (PDF 23-1046), that is, the chemical formula of sodium manganese layered oxide is Na4Mn 14 O 27 · 9H2O. The material was subjected to carbon and sulfur analysis, and its carbon content was 1.82 wt%.

[0124] Example 5

[0125] The preparation method of the carbon-coated hydrated sodium manganese oxide material provided in this embodiment is method (b), which specifically includes the following steps: MnO2, NaOH and glucose are mixed to obtain a mixture according to the molar ratio of manganese element to sodium element of 1:1.5 and the molar ratio of manganese element to carbon element of 1:0.05, and the mixture is kept at 240°C in an argon protective atmosphere for 8 hours to obtain a carbon-coated sodium manganese oxide precursor. The carbon-coated sodium manganese oxide precursor is placed in deionized water and soaked for 12 hours, then filtered, washed to neutrality, and dried to obtain a carbon-coated hydrated sodium manganese oxide material. The carbon-coated hydrated sodium manganese oxide material prepared in this embodiment includes a sodium manganese layered oxide and a carbon coating layer coated on the surface of the sodium manganese layered oxide.

[0126] The carbon-coated hydrated sodium manganese oxide material prepared in this example was subjected to XRD analysis. The analysis results are shown in the attached Figure 6 It was found that the diffraction peak intensity was weak, basically consistent with Na4Mn 14 O 27 9H2O (PDF23-1046) and NaMn6O 12 ·3H2O (PDF 38-0475) corresponds to the sodium manganese layered oxides including Na4Mn 14 O 27 9H2O and NaMn6O 12 · 3H2O. The material was subjected to carbon and sulfur analysis, and its carbon content was 4.27 wt%.

[0127] Example 6

[0128] The preparation method of the carbon-coated hydrated sodium manganese oxide material provided in this embodiment is method (b), which specifically includes the following steps: MnO2, NaOH and tannic acid are mixed to obtain a mixture according to the molar ratio of manganese element to sodium element of 1:1 and the molar ratio of manganese element to carbon element of 1:0.3, and the mixture is kept at 210°C in a nitrogen protective atmosphere for 10 hours to obtain a carbon-coated sodium manganese oxide precursor. The carbon-coated sodium manganese oxide precursor is placed in deionized water and soaked for 15 hours, then filtered, washed to neutrality, and dried to obtain a carbon-coated hydrated sodium manganese oxide material. The carbon-coated hydrated sodium manganese oxide material prepared in this embodiment includes a sodium manganese layered oxide and a carbon coating layer coated on the surface of the sodium manganese layered oxide.

[0129] The carbon-coated hydrated sodium manganese oxide material prepared in this example was subjected to XRD analysis. The analysis results are shown in the attached Figure 7 It was found that due to the low reaction temperature, the diffraction peak intensity was weak, which was basically the same as that of Na4Mn 14 O 27 9H2O (PDF 23-1046) and NaMn6O 12 ·3H2O (PDF 38-0475) corresponds to the sodium manganese layered oxides including Na4Mn 14 O 27 9H2O and NaMn6O 12 · 3H2O. The material was subjected to carbon and sulfur analysis, and its carbon content was 2.84 wt%.

[0130] Example 7

[0131] The preparation method of the carbon-coated hydrated sodium manganese oxide material provided in this embodiment is method (b), comprising the following steps: mixing MnO2, NaOH, and glucose in a molar ratio of manganese to sodium of 1:2 and a molar ratio of manganese to carbon of 1:0.15 to obtain a mixture, and keeping the mixture at 280°C in a helium protective atmosphere for 5 hours to obtain a carbon-coated sodium manganese oxide precursor. The carbon-coated sodium manganese oxide precursor is placed in deionized water and soaked for 12 hours, then filtered, washed to neutrality, and dried to obtain a carbon-coated hydrated sodium manganese oxide material. The carbon-coated hydrated sodium manganese oxide material prepared in this embodiment includes a sodium manganese layered oxide and a carbon coating layer coated on the surface of the sodium manganese layered oxide.

[0132] The carbon-coated hydrated sodium manganese oxide material prepared in this example was subjected to XRD analysis. The analysis results are shown in the attached Figure 8 It was found that the diffraction peaks of Na4Mn 14 O 27 ·9H2O (PDF 23-1046) corresponds to the chemical formula of sodium manganese layered oxide Na4Mn 14 O 27· 9H2O. The material was subjected to carbon and sulfur analysis, and its carbon content was 1.22 wt%.

[0133] Comparative Example 1

[0134] The difference between this comparative example and Example 2 is that the sodium source, manganese source and organic carbon source are directly mixed at once to obtain a mixture, and then the mixture is kept at 1000°C for 3 hours in a helium protective atmosphere for reaction and carbonization, and then the obtained material is immersed in deionized water for 15 hours, and then filtered, washed to neutrality, and dried to obtain a black solid material. The black solid material was subjected to XRD analysis, and the analysis results are shown in the attached Fig. 9 It was found that the diffraction peaks thereof corresponded to MnO (PDF 71-1177), that is, the black solid material prepared in this comparative example did not contain sodium manganese layered oxides, and the carbon-coated hydrated sodium manganese oxide material could not be obtained.

[0135] In this comparative example, the manganese source is MnO2, and the valence of manganese is +4. It can be inferred that the same result will be obtained by using other manganese oxides with lower manganese valence, such as Mn2O3, Mn3O4 and MnO.

[0136] Comparative Example 2

[0137] The difference between this comparative example and Example 2 is that the sodium source and the manganese source are first mixed and calcined to generate sodium manganese oxide, and then mixed with an organic carbon source for carbonization. The material obtained after carbonization was subjected to XRD analysis. The analysis results are shown in the attached Fig.10 It is found that the diffraction peaks correspond to MnO (PDF 71-1177) and Na2CO3 (PDF 37-0451), which shows that Mn in the material exists in the form of MnO and Na exists in the form of soluble salt. Therefore, the carbon-coated hydrated sodium manganese oxide material cannot be obtained in this comparative example.

[0138] Comparative Example 3

[0139] The preparation method of the carbon-coated hydrated sodium manganese oxide material provided in this comparative example is basically the same as that in Example 6, except that the carbonization temperature is replaced with 300°C. The material obtained in this comparative example was subjected to XRD analysis, and the analysis results are shown in the attached Fig.11 It was found that the diffraction peaks corresponded to Mn3O4 (PDF 24-0734), that is, the material prepared in this comparative example did not contain sodium manganese layered oxide, and the carbon-coated hydrated sodium manganese oxide material could not be obtained.

[0140] Experimental example

[0141] The carbon-coated hydrated sodium manganese oxide materials obtained in each embodiment and each comparative example were mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1, and NMP solvent was added thereto and stirred for 5 hours to prepare slurry. The slurry was evenly coated on a stainless steel foil and placed in a vacuum drying oven at 110°C for 8 hours. After drying, cutting, pressing, weighing and other operations were performed to obtain a positive electrode sheet. The mass of the carbon-coated hydrated sodium manganese oxide material in the positive electrode sheet was about 1.5 mg.

[0142] The positive electrode sheets obtained from Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to full battery tests, paired with commercially available aqueous negative electrode material sheets, with a mass ratio of positive and negative active materials of 1:1, and the corresponding electrode sheets were packaged into button batteries, wherein the electrolyte was NaClO4 electrolyte, the diaphragm was a non-woven fabric diaphragm, and the battery shell model was CR2016. The packaged button batteries were tested for their rate performance and cycle performance by a battery testing system. The test voltage range was 0 to 2V, the rate performance current conditions were 0.1A / g, 0.2A / g, 0.5A / g, 1A / g, 2A / g, 5A / g, and 10A / g, respectively, and the cycle performance test conditions were 1A / g. The test results are shown in Table 1. In Table 1, No. 1 represents the discharge capacity of the first cycle, No. 1000 represents the discharge capacity of the 1000th cycle, and No. 2000 represents the discharge capacity of the 2000th cycle.

[0143] The positive electrode sheets obtained in Examples 5 to 7 and Comparative Example 3 were subjected to three-electrode constant current charge and discharge tests, respectively. The electrolyte was 17 mol / kg NaClO4 electrolyte, the reference electrode was a calomel electrode, the counter electrode was a platinum electrode, the test voltage range was 0 to 1.2 V, and the current conditions were 0.1 A / g, 0.2 A / g, 0.5 A / g, 1 A / g, 2 A / g, 5 A / g, and 10 A / g, respectively. The test results are shown in Table 2.

[0144] Table 1 Rate and cycle discharge specific capacity performance test results (unit: mAh / g)

[0145]

[0146]

[0147] Table 2 Constant current charge and discharge discharge specific capacity performance test results (unit: mAh / g)

[0148] Group 0.1A / g 0.2A / g 0.5A / g 1A / g 2A / g 5A / g 10A / g Example 5 101.5 91.8 85.0 80.1 73.4 62.2 51.0 Example 6 99.3 89.8 82.2 77.3 71.5 59.8 47.4 Example 7 107.3 91.1 81.5 74.4 68.1 58.0 46.8 Comparative Example 3 66.8 54.0 50.2 48.1 43.8 41.2 38.3

[0149] It can be seen from Table 1 that the full battery assembled using the carbon-coated hydrated sodium manganese oxide material prepared by the method of the present invention as the positive electrode material has a higher discharge specific capacity, higher rate performance and better cycle performance.

[0150] It can be seen from Table 2 that the carbon-coated hydrated sodium manganese oxide material prepared by the method of the present invention has a higher discharge specific capacity.

[0151] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for preparing a carbon-coated hydrated sodium manganese oxide material, characterized in that: The method comprises at least one of the following methods (a) and (b): (a) mixing a manganese source and an organic carbon source, and carbonizing the mixture at 600 to 1100° C. in an inert atmosphere to obtain a first precursor of a carbon-coated manganese source; mixing the first precursor with a sodium source, and calcining and reacting the mixture at 250 to 400° C. in an oxygen-containing atmosphere to obtain a second precursor; soaking the second precursor in water, and then washing and drying the mixture to obtain a carbon-coated hydrated sodium manganese oxide material; (b) mixing a manganese source, a sodium source and an organic carbon source, reacting and carbonizing the mixture at 210-280° C. in an inert atmosphere to obtain a carbon-coated sodium manganese oxide precursor; soaking the carbon-coated sodium manganese oxide precursor in water, and then washing and drying the mixture to obtain a carbon-coated hydrated sodium manganese oxide material.

2. The method for preparing the carbon-coated hydrated sodium manganese oxide material according to claim 1, characterized in that: In method (a), at least one of the following conditions is met: (1) The manganese source includes at least one of MnO2, Mn2O3, Mn3O4 and MnO; (2) the organic carbon source comprises at least one of glucose, sucrose, citric acid and tannic acid; (3) The sodium source includes NaOH.

3. The method for preparing the carbon-coated hydrated sodium manganese oxide material according to claim 1, characterized in that: In method (a), at least one of the following conditions is met: (1) The molar ratio of the manganese element in the manganese source to the carbon element in the organic carbon source is 1:0.15-0.5; (2) The molar ratio of the manganese element in the manganese source to the sodium element in the sodium source is 1:1-2.

4. The method for preparing the carbon-coated hydrated sodium manganese oxide material according to claim 1, characterized in that: In method (a), at least one of the following conditions is met: (1) The carbonization time is 2 to 5 hours; (2) The gas in the inert atmosphere includes at least one of nitrogen, argon and helium; (3) The calcination time is 5 to 15 hours; (4) The soaking time is ≥ 12 h.

5. The method for preparing the carbon-coated hydrated sodium manganese oxide material according to claim 1, characterized in that: In method (b), at least one of the following conditions is met: (1) The manganese source includes MnO2; (2) the sodium source comprises NaOH; (3) The organic carbon source includes at least one of glucose and tannic acid.

6. The method for preparing the carbon-coated hydrated sodium manganese oxide material according to claim 1, characterized in that: In method (b), at least one of the following conditions is met: (1) The molar ratio of the manganese element in the manganese source to the sodium element in the sodium source is 1:1-2; (2) The molar ratio of the manganese element in the manganese source to the carbon element in the organic carbon source is 1:0.05-0.

3.

7. The method for preparing the carbon-coated hydrated sodium manganese oxide material according to claim 1, characterized in that: In method (b), at least one of the following conditions is met: (1) The carbonization time is 5 to 10 hours; (2) The gas in the inert atmosphere includes at least one of nitrogen, argon and helium; (3) The soaking time is ≥ 12 h.

8. The carbon-coated hydrated sodium manganese oxide material obtained by the method for preparing the carbon-coated hydrated sodium manganese oxide material according to any one of claims 1 to 7, characterized in that: The carbon-coated hydrated sodium manganese oxide material comprises a sodium manganese layered oxide and a carbon coating layer coated on the surface of the sodium manganese layered oxide; The sodium manganese layered oxide includes Na4Mn 14 O 27 9H2O, NaMn6O 12 ·3H2O and Na 0.55 At least one of Mn2O4·1.5H2O; The carbon content of the carbon-coated hydrated sodium manganese oxide material is 0.2 wt.% to 6 wt.%.

9. A positive electrode sheet, characterized in that: The invention comprises a carbon-coated hydrated sodium manganese oxide material prepared by the method for preparing a carbon-coated hydrated sodium manganese oxide material according to any one of claims 1 to 7, or a carbon-coated hydrated sodium manganese oxide material according to claim 8.

10. A sodium ion battery, characterized in that Comprising the positive electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Method for preparing carbon-coated manganite composite material

    CN103606654A